Cholinergic neurodegeneration and cholesterol metabolism dysregulation by constitutive p75NTR signaling in the p75exonIII-KO mice - Comaposada-Baró, Raquel; Benito-Martínez, Andrea; Escribano-Saiz, Juan Julian; Franco, María Luisa; Ceccarelli, Lorenzo; Calatayud-Baselga, Isabel; Mira, Helena; Vilar, Marçal (Frontiers in Molecular Neuroscience, 2023)
Degeneration of basal forebrain cholinergic neurons (BFCNs) is a hallmark of Alzheimer's disease (AD).However, few mouse models of AD recapitulate the neurodegeneration of the cholinergic system. The p75 neurotrophin receptor, p75 NTR , has been associated with the degeneration of BFCNs in AD. The senescenceaccelerated mouse prone number 8 (SAMP8) is a well-accepted model of accelerated and pathological aging.To gain a better understanding of the role of p75 NTR in the basal forebrain during aging, we generated a new mouse line, the SAMP8-p75 exonIII-/-. Deletion of p75 NTR in the SAMP8 background induces an increase in the number of BFCNs at birth, followed by a rapid decline during aging compared to the C57/BL6 background. This decrease in the number of BFCNs correlates with a worsening in the Y-maze memory test at 6 months in the SAMP8-p75 exonIII-/-. We found that SAMP8-p75 exonIII-/-and C57/BL6-p75 exonIII-/-mice expressed constitutively a short isoform of p75 NTR that correlates with an upregulation of the protein levels of SREBP2 and its targets, HMGCR and LDLR, in the BF of both SAMP8-p75 exonIII-/-and C57/BL6-p75 exonIII-/-mice. As the neurodegeneration of the cholinergic system and the dysregulation of cholesterol metabolism are implicated in AD, we postulate that the generated SAMP8-p75 exonIII-/-mouse strain might constitute a good model to study long-term cholinergic neurodegeneration in the CNS. In addition, our results support the role of p75 NTR signaling in cholesterol biosynthesis regulation.